The Ecology of the Little Owl in European Farmland - Chrenková, Monika (Jihočeská univerzita, 2021)
The little owl population in the most of Europe is rapidly declining mainly due to dramatic changes and transformation of the agricultural landscape, which resulted in the loss of suitable foraging habitats. Due to rapid population decline and range contraction, urgent conservation measures have to be implemented to save the population from extinction in certain areas. The thesis aims were to identify long-term population trend in selected regions, to uncover the habitat selection of breeding birds and to evaluate the effectiveness of individual management measures for the little owl conservation in the European farmland. The research on population status in Czech Republic and Slovakia revealed long-term population decline and marked distributional range contraction of the little owl, documenting its rapid local extinctions over the last two decades. On the contrary, results from Hortobagy National Park,representing the first large-area systematic survey in Hungary, indicate high population density and its widespread distribution. In particular, the study uncovers one of the highest population densities of this species from an agricultural landscape in Central Europe. Further detailed investigation of habitat selection at three different scales shows the link between certain habitat characteristics and species occurrence and supports the hypothesis of agriculture intensification being the main driver of the population decline of little owl in the Central Europe. Finally, the thesis provides evidence on the effect of different conservation management measures on little owl population in Denmark, where the species is close to extinction. Research findings indicate that food limitation during the breeding season may be the main reason for the declining numbers of little owls in Denmark. To prevent little owl extinction, evidence based conservation measures, such as provision of suitable foraging habitats with high availability and good accessibility of prey close to nests, are inevitable.
The Ecology of the Little Owl in European Farmland
Keywords: farmland birds; population density; population trend; distribution; habitat associations; spatial behaviour; little owl; breeding places; conservation measures; farmland birds; population density; population trend; distribution; habitat associations; spatial behaviour; little owl; breeding places; conservation measures